2014
DOI: 10.1016/j.cmet.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The Complement Inhibitor CD59 Regulates Insulin Secretion by Modulating Exocytotic Events

Abstract: Type 2 diabetes is triggered by reduced insulin production, caused by genetic and environmental factors such as inflammation originating from the innate immune system. Complement proteins are a component of innate immunity and kill non-self cells by perforating the plasma membrane, a reaction prevented by CD59. Human pancreatic islets express CD59 at very high levels. CD59 is primarily known as a plasma membrane protein in membrane rafts, but most CD59 protein in pancreatic β cells is intracellular. Removing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 23 publications
2
58
1
1
Order By: Relevance
“…3D). Taken together, these results fail to support a role for CD55 in the control of insulin secretion and point out an interesting dichotomy between CD55 and CD59 [10] as to their roles in this respect.…”
Section: Insulin Secretion Is Unaffected By Silencing Of Cd55contrasting
confidence: 62%
See 2 more Smart Citations
“…3D). Taken together, these results fail to support a role for CD55 in the control of insulin secretion and point out an interesting dichotomy between CD55 and CD59 [10] as to their roles in this respect.…”
Section: Insulin Secretion Is Unaffected By Silencing Of Cd55contrasting
confidence: 62%
“…1A). A recent publication has shown that CD55 is expressed in pancreatic human islets and also in Wistar and diabetic GK rat islets [10]. Further, in the same study it was observed that expression of CD55 had a tendency for increase in the diabetic (GK) rat islets as compared to the healthy control (Wistar) islets.…”
Section: Expression Of Complement Genes In Ins1 832/13 Cells Human Amentioning
confidence: 84%
See 1 more Smart Citation
“…Because vitamin A dimers cause cholesterol accumulation in the RPE (20,21), they could potentially interfere with CD59 trafficking. To follow CD59 recycling, we treated RPE monolayers with phosphatidylinositol-specific phospholipase C (PI-PLC), which removes cell surface GPI-APs such as CD59 (23). Cell surface CD59 was completely restored ∼60 min after In the x-z images, ZO-1 (red) demarcates apical (Ap) and basolateral (Bl) cell membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Formaldehyde-fixed, paraffinembedded mouse pancreatic sections (5 μm thick) were obtained from mice fed with ND or HFD (for 16 weeks) as well as Gcgr −/− mice. After dewaxing of the sections, the antibody- Analysis of gene expression Gene expression analysis was carried out by microarray on cDNA from islets of 23 type 2 diabetic donors and 23 non-diabetic donors matched for age, sex and BMI, using the Affymetrix GeneChip Human Gene 1.0 ST whole-transcript assay as previously described [18,19]. The data were summarised and normalised with the robust multi-array analysis method using the Expression Console software package (Affymetrix, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%